Damage evolution in marble under uniaxial compression monitored by Pressure Stimulated Currents and Acoustic Emissions (Fracture and Structural Integrity, 2019)
The spatiotemporal evolution of damage in marble specimens under uniaxial compression is monitored using Pressure Stimulated Currents (PSCs) and Acoustic Emissions (AEs). The novelty of the study is the use of an integrated grid of sensors (instead of a single pair of electrodes) to detect the weak electrical signals, emitted during loading. The use of such a grid of sensors does indeed enhance the capabilities of the PSC technique providing valuable information about the initiation and propagation of micro-fracturing at the interior of the specimens. The experimental results indicate that both the improved b-value of the AE hits and the energy of the PSCs offer information about the proximity of the applied stress to that causing fracture. It is thus concluded that both quantities could be considered as pre-failure indicators.
Keywords: Pressure Stimulated Currents; Acoustic Emissions; Improved b-value; Damage evolution; Uniaxial compression; Marble